Slovenian health care system performance in the light of Euro Health Consumer Index 2012 - Farkas, Jerneja; Albreht, Tit; Zaletel-Kragelj, Lijana (Anali PAZU, 2022)
Health care systems are complex entities with several stakeholders that include patients, health care providers, payers, regulators and government. For lay and professional public, the methodology of health care system performance analysis, result interpretation and translation to policy making is not well understood. Slovenian health care system performance results from a Swedish health care analyst (Euro Health Consumer Index 2012) and opportunities for improvement are discussed. We specifically addressed methodological challenges of international health care system performance comparisons.
Keywords: comparison; health care system; indicators; Slovenia